Narrow distance inter-pregnancies increase the incidence of Post-Partum hemorrhage - Nadhira Farah Puspitasaria; Rachmiyani, Irmiya (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2022)
Background and Aims. Maternal Mortality Rate (MMR) is the parameters of women's health status in community. The single most common cause of maternal mortality is obstetric haemorrhage, generally occurring postpartum. Most postpartum haemorrhage cases are caused by uterus atony, myometrium tonus loss, placenta retention, and clotting disorders. Short pregnancy intervals can cause threefolds of anaemia than normal pregnancy intervals. Pregnant women who suffer from anaemia has the possibility experiencing a postpartum bleeding caused by atonia uteri. This research aims to acknowledge the effect of narrow distance interpregnancy on a postpartum haemorrhage. Methods. This study uses an observational analytic study with a cross